Synthesis, DNA binding and antitrypanosomal activity of benzimidazole analogues of DAPI. Issue 24 (15th December 2016) - Farahat, Abdelbasset A.; Bennett-Vaughn, Cheree; Mineva, Ekaterina M.; Kumar, Arvind; Wenzler, Tanja; Brun, Reto; Liu, Yang; Wilson, W. David; Boykin, David W.
Graphical abstract: Highlights: New analogues of the antitrypanosomal agent DAPI were made. ΔTm of some of the final amidines was superior than that of DAPI. Compounds5b and15a showed superior antitrypanosomal activity compared to the parentI . Abstract: A series of novel benzimidazole diamidines were prepared from the corresponding dicyano analogues either by applying Pinner methodology (5a –c, 10 and13a ) or by making amidoximes intermediates that were reduced to the corresponding amidines (15a –c ). The new amidines were evaluated in vitro against the protozoan parasite Trypanosoma brucei rhodesiense ( T. b. r .). The thiophene analogue5b and the N -methyl compound15a showed superior antitrypanosomal activity compared to that of the parentI .